The learning cycle the 21st century and millennial learners : who they are and how to teach them - McCarthy, Bernice (Wauconda, IL About Learning, Inc., 2012)
Describes the 4MAT Learning Cycle as a teaching system.
Introduction -- The 21st century Millennial learners -- The learning cycle, neuroscience and the Millennials -- The 21st century curriculum : competencies, concepts and the Common Core -- Assessing around the learning cycle -- The endurance and continuity of the learning cycle.
Includes bibliographical references (pages 187-191) and index.
Keywords: 4MAT system; Learning; Learning, Psychology of